Against All Odds: How Rituals Sustain Engagement with Intractable Social Problems - Frey‐Heger, Corinna; Gatzweiler, Marian Konstantin; Barrett, Michael (Journal of Management Studies, 2026)
Being confronted with seemingly intractable problems such as refugee crises, climate change, or poverty is daunting and can risk a sense of meaninglessness for organizational actors working on these issues. We focus on the pervasive use of representations, including assessments and evaluations, to deal with intractable problems, even though such representations are commonly understood as incomplete or flawed. Drawing on ritual theory, we approach representations as powerful in creating meaning and sustaining action, irrespective of a direct link to the problem. Our ethnographic study focuses on a humanitarian organization and their work in refugee crises. We unpack how ritualized representations, specifically the ritualistic use of needs assessments, generate meaning beyond their narrowly intended functionality. Through their shared rhythm, emotional intensity, and ceremonial display, ritualized representations sustain engagement against all odds in the face of otherwise intractable problems. We contribute to debates on sustaining engagement with complex social problems through ritualization and develop a more nuanced understanding of the double‐edged nature of ritualized practices.